Gender-dependent variations in optical illusions: evidence from N400 waveforms. (2nd October 2020) - Papageorgiou, Charalabos; Stachtea, Xanthi; Papageorgiou, Panos; Alexandridis, Antonio T; Makris, Gerasimos; Chrousos, George; Kosteletos, George
Abstract: Objective : The cognitive mechanisms (especially the gender-related ones) underlying optical illusion processing remain elusive. Since the N400 component of event-related potentials (ERPs) is an index of the semantic integration of information processing tasks, the present study focuses on gender-related differences in N400 waveforms elicited during the reasoning process applied to reach a valid conclusion of optical illusions engaging working memory (WM). Approach : Fifty-one healthy participants (28 males, age = 34.25 years ± 10.25, years of education = 16.00 years ± 1.78; and 23 females, age = 33.43 ± 7.93, years of education = 15.56 ± 1.82) were measured. The N400 ERP component was evoked by 39 optical illusions adjusted to induce WM. We compared brain activation patterns while participants maintained conclusions of the optical illusions in WM. The N400 of ERPs was recorded during the WM phase, during which participants were required to draw a logical conclusion regarding the correctness of the optical illusions. Main results : Analysis revealed that females compared to males exhibited significantly increased N400 amplitudes located at parietal and occipital sites, whereas males exhibited significantly higher N400 amplitudes located at frontal areas. Furthermore, females compared to males demonstrated significantly prolonged latencies of the N400 component located at right frontotemporal abductions. Significance: These results suggest that coupling of optical illusions with WM engages distinct gender-related variations of brain semantic processing as reflected by the N400 ERP component. Based on the dual process account, our study gives support to the notion that women tend to employ a more deliberate and slower semantic reasoning than the men who tend to employ an automatic and fast one. Topographically, within the network sub-serving the semantic operation, the posterior brain areas responsible for sensorimotor integration-related processes elicit a greater brain activation among females while the anterior brain areas responsible for control and storage/retrieval operation elicit a greater brain activation among males.